Comparison Of Outdoor and Indoor Playground Qualifications of State and Private Kindergartens: Case of Malatya Province - Mehmet Güllü; Ecesu Özcan (Türk Spor ve Egzersiz Dergisi)
In this study, it is aimed to contribute to the determination of the most appropriate spatial dimensions by comparing the dimensions of the indoor and outdoor playgrounds in private kindergartens and public kindergartens in Malatya. In this study, document analysis method was used. When the research findings are examined, it is seen that although there are not specifically multi-purpose halls in public schools other than classrooms, the playgrounds of public kindergartens have large areas where students can engage in activities comfortably compared to private institutions. Again, it has been found that public kindergartens have larger areas in indoor playgrounds compared to private kindergartens regarding quotas, in terms of quota based area measurements.In future research, applying motor skill tests to children studying in public kindergartens and private kindergartens, which have two different service standards, will provide detailed and targeted answers about field competencies from the results achieved.